2019
DOI: 10.1109/access.2019.2908340
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Spurious Mode Compensation for AlN Lamb Wave Resonators

Abstract: Lamb wave modes with type I dispersion characteristics exhibit strong affinity toward multi transverse modes behavior above resonance frequency (f r) in the AlN Lamb wave resonators (LWRs), especially the high-transduction-efficiency modes: S 0 and S 1 mode. For conventional interdigital transducer (IDT) design, the IDT aperture and IDT gap are the two main factors impacting the transverse mode placements and strengths, according to the wave vector analysis and finite element method (FEM) simulation. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…a multi-mode character and conversion to other modes on the boundaries of non-uniformities [14], [16]- [20]. The dispersion phenomenon leads to presence of two types of interrelated velocities -phase and group, both frequencies dependent and characterized by dispersion curves [21]- [22]. As the different frequency components propagate with different velocities after some distance they are concentrated in different UGW signal parts in the time domain [23].…”
Section: Introductionmentioning
confidence: 99%
“…a multi-mode character and conversion to other modes on the boundaries of non-uniformities [14], [16]- [20]. The dispersion phenomenon leads to presence of two types of interrelated velocities -phase and group, both frequencies dependent and characterized by dispersion curves [21]- [22]. As the different frequency components propagate with different velocities after some distance they are concentrated in different UGW signal parts in the time domain [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are some other design strategies, which are based on more abrupt geometric modifications, proposed to reduce anchor loss, such as using beveled, rounded or chamfered corners at the ends of the resonator bodies [ 115 , 116 , 117 ] and introducing etched slots or holes [ 118 , 119 ], but the broad applicability of these methods to different operating frequencies has not been investigated to date. Another strategy to enhance Q involves designing the electrical excitation configuration to suppress spurious modes which could carry the acoustic energy away from the resonator body [ 120 , 121 ]. This Q-enhancement strategy is attractive for LVRs using more anisotropic piezoelectric materials as the resonator body.…”
Section: Discussionmentioning
confidence: 99%
“…Some design strategies based on local etching were also proposed to reduce anchor loss such as introducing etched slots [ 118 ] or etched holes [ 119 ] as shown in Figure 8 g,h. Apart from the strategies mentioned above, making modification to IDT electrodes were also proposed as an effective means to suppress spurious resonances and thus enhance Q [ 120 , 121 ]. Giovannini et al [ 120 ] demonstrated a 1.2× enhancement of Q in a 889-MHz AlN LVR using apodized electrode configuration as shown in Figure 8 i.…”
Section: Q-enhancement Strategies For Lvrsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] But in order to achieve a high quality (Q) factor, the piezoelectric layer cannot be too thin and the fabrication techniques are elaborate, resulting in the limited frequency and high cost. Lamb wave devices which combine the strengths of SAW devices and BAW devices have been the hot area of research in recent years [16][17][18][19][20][21], but the process flow of fabrication is even more complicated than that of BAW devices. Aiming at lowering the cost, many researchers are committed to the study of high frequency SAW devices.…”
Section: Introductionmentioning
confidence: 99%